If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5y + -2) = -21 Reorder the terms: 3(-2 + 5y) = -21 (-2 * 3 + 5y * 3) = -21 (-6 + 15y) = -21 Solving -6 + 15y = -21 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 15y = -21 + 6 Combine like terms: -6 + 6 = 0 0 + 15y = -21 + 6 15y = -21 + 6 Combine like terms: -21 + 6 = -15 15y = -15 Divide each side by '15'. y = -1 Simplifying y = -1
| 18=8.4 | | 4(2u+3)+4u+2=6(u-1)-4u | | f=p(1+rt) | | 8x^3+x^2-72x-9=0 | | 3x+7=2x+11 | | 70n-50n=80 | | 3(3u+2)+5u=6(u-4)-26 | | 8k-14=16 | | 7y-2=5y+8 | | 2(s-4)-7=19 | | 7+7c=6c-18 | | 18=-2(2x-7) | | 8x+2=9x+12 | | 2(5y-4)=32 | | 9y-6+y+8=42 | | 4.1+1.8n=0.14 | | 7x*4=12 | | 25+15x=100 | | 4x+5=7x | | 21+x=2x-36 | | A+(A+9)=99 | | 4b-10=6b | | 3n=m+1 | | 9c+1=-26 | | 4x-9=24 | | -9c+1= | | 6x+10=8x+5 | | 15+X=2X-38 | | c^2=6c | | -2y=1+x | | 9b-9=3d-3 | | 16-4c=20 |